2004
DOI: 10.1557/proc-830-d2.2
|View full text |Cite
|
Sign up to set email alerts
|

Step Coverage and Composition of Pb(Zr, Ti)O3 Capacitors Prepared on Sub-Micron Three-Dimensional Trench Structure by Metalorganic Chemical Vapor Deposition

Abstract: Pb(Zr, Ti)O3 (PZT) films were deposited into sub-micron trench structure consisting of SiO2/TiAlN/Ti/SiO2/Si to investigate their thickness and composition conformality by pulsed-metalorganic chemical vapor deposition (MOCVD) using liquid delivery source-supply system. Bis(dipivaloylmethanato)lead [Pb(DPM)2], tetrakis(1-methoxy-2-methyl-2-propoxy)zirconium [Zr(MMP)4] and tetrakis(1-methoxy-2-methyl-2-propoxy)titanium [Ti(MMP)4] were used as Pb, Zr and Ti source materials, respectively. In Arrhenius plot, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The isotropic flow of precursor molecules accounts for the good step coverage of MOCVD in contrast to most physical vapor deposition processes with a straightforward flight of elements from a point source to the substrate. In the case of 3D deposition of binary oxide films, such as HfO 2 and Ta 2 O 5 for capacitor applications, the homogeneity of film thickness is central, while uniformity in cation composition becomes an additional issue for multicomponent films. Recent studies have indicated a serious problem in that multicomponent oxide films deposited over 3D structures by MOCVD exhibit nonuniformity in cation composition, although film thickness appears to be uniform over the complex structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The isotropic flow of precursor molecules accounts for the good step coverage of MOCVD in contrast to most physical vapor deposition processes with a straightforward flight of elements from a point source to the substrate. In the case of 3D deposition of binary oxide films, such as HfO 2 and Ta 2 O 5 for capacitor applications, the homogeneity of film thickness is central, while uniformity in cation composition becomes an additional issue for multicomponent films. Recent studies have indicated a serious problem in that multicomponent oxide films deposited over 3D structures by MOCVD exhibit nonuniformity in cation composition, although film thickness appears to be uniform over the complex structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated a serious problem in that multicomponent oxide films deposited over 3D structures by MOCVD exhibit nonuniformity in cation composition, although film thickness appears to be uniform over the complex structure. [1][2][3][4] In MOCVD, surface reaction limiting deposition, where the deposition rate depends only on the substrate temperature, has been a common approach to achieving a homogeneous 3D coverage. However, at a mutual deposition temperature, not every precursor necessarily decomposes under the surface-reaction limiting condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb(C 11 4 [tetrakis (1-methoxy-2-methyl-2-propoxy) zirconium, Zr(MMP) 4 ] (Asahi Denka Kogyo K. K.), and Ti(OC(CH 3 ) 2 CH 2 OCH 3 ) 4 [tetrakis(1-methoxy-2-methyl-2-propoxy)titanium, Ti(MMP) 4 ] (Asahi Denka Kogyo K. K.) were used as the respective Pb, Zr, and Ti source materials [10,11]. Ethylcyclohexane and O 2 gas were used as a solvent and as an oxidant, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the replacement of conventional planar capacitors, recent developments have been oriented toward integration of three-dimensional capacitors (Goux, Russo et al, 2005;Scott, 2005a,b;Scott et al, 2005;Nagel et al, 2004;Joshi, 2004;Narayan, 2003;Zambrano, 2003;Johnson et al, 2003). Lead zirconate titanate (PbZr 1Àx Ti x O 3 , PZT) is the most used ferroelectric material for planar capacitors and is also used for three-dimensional capacitor scaling (Nagai et al, 2006(Nagai et al, , 2005; Koo et al, 2005;Kim et al, 2005;Funakubo et al, 2005). Nevertheless, much attention is also focused on the integration of strontium bismuth tantalate (SrBi 2 Ta 2 O 9 , SBT) in threedimensional capacitors or in nanotubes (Morrison et al, 2003).…”
Section: Introductionmentioning
confidence: 99%